GREEN MARKETING, BRAND IMAGE DAN PENGARUHNYA PADA KEPUTUSAN PEMBELIAN - Maulidia, Ayu Naina; Putri, Kartika Anggraeni Sudiono (LPPM STIE Muhammadiah Bandung, 2023)
The purpose of this study is to assess the impact of Green Marketing and Brand Image on Avoskin Beauty product purchasing decision in Malang City. In this study, a quantitative technique with descriptive analysis was applied. This sample of this research consisted of 140 respondents who were Avoskin Beauty customers in Malang City. The data was collected using a non-probability sampling method with a purposive sampling approach. SPSS was used to analyze the data, which included multiple linear regression analysis, partial tests, and simultaneous tests. The findings of this study suggest that Green Marketing and Brand Image have an impact on consumer purchasing decisions for Avoskin Beauty products in Malang City, either partially or concurrently.